Limited Investment Capital and Credit Spreads - SIRIWARDANE, EMIL N. (Journal of Finance, 2019)
ABSTRACT Using proprietary credit default swap (CDS) data, I investigate how capital shocks at protection sellers impact pricing in the CDS market. Seller capital shocks—measured as CDS portfolio margin payments—account for 12% of the time‐series variation in weekly spread changes, a significant amount given that standard credit factors account for 18% during my sample. In addition, seller shocks possess information for spreads that is independent of institution‐wide measures of constraints. These findings imply a high degree of market segmentation, and suggest that frictions within specialized financial institutions prevent capital from flowing into the market at shorter horizons.